2013
DOI: 10.1080/10508406.2012.748664
|View full text |Cite
|
Sign up to set email alerts
|

Using Concept Maps to Facilitate Collaborative Simulation-Based Inquiry Learning

Abstract: This study investigates the effect of a shared concept-mapping task on high school students' learning about kinematics in a collaborative simulation-based inquiry setting. Pairs of students were randomly assigned to a concept-mapping condition (12 pairs) or a control condition (13 pairs). Students in the concept-mapping condition had a computer-supported collaborative concept-mapping tool that aimed to integrate concepts and propositions. Students in the control condition used the same learning environment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 63 publications
(77 reference statements)
1
35
0
1
Order By: Relevance
“…When the information was presented to students' eyes, they could begin to process the information in the visual channel. The finding supported studies that representations of scientific concepts were effective in consolidating students' learning (Gijlers et al, 2013;Jari et al, 2014;Vreman-de Olde et al, 2013). In addition, in the ILIS learning setting, when students made presentations to explain their claims, in-depth conceptual understandings had taken place in the combination of verbals and visual materials, rather than isolated from one another (Mayer et al, 1992).…”
Section: The Combination Of Phet Simulations With Inquiry-based Instrsupporting
confidence: 82%
See 1 more Smart Citation
“…When the information was presented to students' eyes, they could begin to process the information in the visual channel. The finding supported studies that representations of scientific concepts were effective in consolidating students' learning (Gijlers et al, 2013;Jari et al, 2014;Vreman-de Olde et al, 2013). In addition, in the ILIS learning setting, when students made presentations to explain their claims, in-depth conceptual understandings had taken place in the combination of verbals and visual materials, rather than isolated from one another (Mayer et al, 1992).…”
Section: The Combination Of Phet Simulations With Inquiry-based Instrsupporting
confidence: 82%
“…The findings from this current study are supportive of the theory of Lev Vygotsky (1978) and empirical studies. It suggests that optimal learning is achieved when the series of activities are supported by either a capable person (Gijlers et al, 2013;Heift et al, 2001;Mitrovic, 2003;Roscoe et al, 2007), cooperatively working with peers (Duffy et al, 1998;Webb, 1982), or scaffolded by technology tools (Azevedo et al, 2004;Hmelo-Silver, 2006;Hmelo-Silver et al, 2007), regardless of whether they are male or female students.…”
Section: Male Students Did Not Benefit From Ilis Approach Interventiomentioning
confidence: 99%
“…The ISIA classrooms provided different types of verbal information (such as teacher's questions and lectures and students' discussions and explanations) to support students seeking to make sense of a specific concept. Research suggests that language can help students to understand and acquire the terms needed to describe relevant phenomena properly [61,62]. When students used PhET simulations to test their hypothesis, dynamic animations, images, charts, tables showing on the computer interface and printed words on textbooks helped to scaffold students' understanding.…”
Section: Isia Intervention Enhanced Students' Conceptual Learning Inmentioning
confidence: 99%
“…Sun, Looi, and Xie () analysed students' interactions when working collaboratively in a simulation‐based inquiry environment and found that students were highly engaged, while the low prior knowledge students profited especially from the interaction. Gijlers and de Jong (), studying students in a collaborative online learning environment around a simulation on one‐dimensional kinematics, found that students' integration‐building exchanges were positively related to their knowledge gains. In a recent study, however, Chang et al () found that not all collaborative groups learning with an online simulation were able to engage in a productive collaboration process; obviously, collaboration between students also needs to be trained or supported.…”
Section: The Next Steps In Technology‐based Guidance Of the Inquiry Pmentioning
confidence: 99%